A STUDY ON BUTTERFLY BIODIVERSITY OF JOGIMATTI FOREST, CHITRADURGA, KARNATAKA-INDIA - DHANANJAYA, S. G.; ROOPA, K.; NAIK, K. L. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
A pilot study was carried out to know the biodiversity of butterflies in the Jogimatti Forest of Chitradurga district, Karnataka, India during 2018. Butterflies from their aesthetic appeal, they are good pollinators, highly sensitive to any environmental fluctuation and they act as good bio-indicators of the health of their habitat. The survey revealed presence of 39 species of butterflies belong to 5 different families, dominated by Nymphalidae (44%), Pieridae (28%), Lycaenidae (13%) Papilionidae (10%) and Hespiridae (5%) With respect to species number and total 430 Nymphalidae (136) and Pieridae (178) butterflies are more. Present findings revealed Common mormon, Common emigrant, Plain tiger, Common cerulean and Indian cupid are the dominanat butterfly species from their respective families. These results suggests that Jogimatti forest of Chitradurga district has a favourable environmental condition that accommodates butterfly diversity.